2010
DOI: 10.1007/bf03355486
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation on the Effect of Copper Upon Eutectoid Transformation of As-Cast and Austenitized Spheroidal Graphite Cast Iron

Abstract: Copper is known as a pearlite promoter in cast iron and has been used as such for a long time, most often together with low amounts of manganese. Literature data, however, has shown that these two elements act differently on the ferritic and pearlitic transformations. In order to provide more insight in the role of this element on the solid-state transformation of spheroidal graphite (SG) cast iron, this paper investigates the effect of adding copper in small step increments, from 0.11 to 1 wt. % Cu, to SG iro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 4 publications
(5 reference statements)
2
41
1
2
Order By: Relevance
“…This latter effect has been also reported by Sertucha et al [7], as shown in figure 3 where the results of Neumeier et al [2], for alloys without tin have been plotted as well for comparison. It is quite possible that the shift of the transition from 0.6 wt.% Cu according to Sertucha et al [7], to 0.5 wt.% for Neumeier et al [2], relates to the associated increase in the manganese content from 0.15 wt.% to 0.27 wt.%. Results from Pan et al [5], for various manganese contents have been also reported in figure 3.…”
Section: Literature Reviewsupporting
confidence: 82%
See 2 more Smart Citations
“…This latter effect has been also reported by Sertucha et al [7], as shown in figure 3 where the results of Neumeier et al [2], for alloys without tin have been plotted as well for comparison. It is quite possible that the shift of the transition from 0.6 wt.% Cu according to Sertucha et al [7], to 0.5 wt.% for Neumeier et al [2], relates to the associated increase in the manganese content from 0.15 wt.% to 0.27 wt.%. Results from Pan et al [5], for various manganese contents have been also reported in figure 3.…”
Section: Literature Reviewsupporting
confidence: 82%
“…Effect of copper on ferrite fraction. Results from Pan et al [5] and Sertucha et al [7] are for TA cups, those from Neumeier are for keel-blocks [2] Neumeier et al could plot all their results along a single curve when considering (w Sn + 0.1w Cu ) as abscissa where w i is the mass fraction of element i, in % [2]. Following this, an attempt to defining an index of pearlite promoting elements was made using the whole set of data from Pan et al on TA cups [5].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach has been applied successfully to explain that Cu and Mn favour pearlite because they both decrease the driving force for carbon diffusion in ferrite and decrease more Tα than Tp. 9,10) Using the same hypothesis, this approach was extended to the reverse eutectoid transformation.…”
Section: Introductionmentioning
confidence: 99%
“…47 (4), JuLIO-AgOsTO, 307-318, 2011, IssN: 0034-8570, eIssN: 1988-4222, doi: 10.3989/revmetalm.1044 y tipo de elementos residuales aportados por las materias primas utilizadas. La presencia de muchos de estos elementos en concentraciones minoritarias influye directamente en la germinación y crecimiento del grafito [4][5][6][7] , condiciona en gran medida la evolución de la matriz metálica durante el proceso de enfriamiento en el estado sólido [8][9][10] , provoca la aparición de fenómenos de segregación durante la solidificación [11 y 12] y, en muchos casos, favorece la formación de carburos metálicos [13] . Por todo ello, la aportación de estos elementos químicos residuales afecta a las características estructurales de las piezas y condiciona sus propiedades mecánicas [8 y 13] .…”
Section: Introductionunclassified